Epidemiological-clinical characteristics and results of appendiceal plastron management in adult patients from a reference hospital in Peru : Características epidemiológico-clínicas y resultados del manejo de plastrón apendicular en pacientes adultos de un hospital de referencia del Perú - Cehua Alvarez, Efrain (2023)
Introduction: Appendicular plastron is considered a progressive form of acute appendicitis, with a national prevalence of 2-10%. Currently management is often controversial. It is that from this context, it seeks to promote studies that can elucidate the variables associated with the management of this condition. Objective: to determine the epidemiological-clinical characteristics associated with the results of the management of the appendiceal plastron in adult patients in a reference hospital in Peru. Methods: Non-experimental study, with a quantitative approach, observational, analytical and cross-sectional design, whose sample consisted of 100 patients with a diagnosis of appendicular plastron. The data collection sheet was applied as an instrument. Likewise, a Poisson regression model was used to respond to the objectives. Results: The multivariate analysis showed that alcohol consumption (p<0.05 RPa=1.12), nausea and vomiting (p<0.05, RPa=1.48), diarrhea (p<0.05; RPa=1.08), duration of symptoms before admission between 3 and 5 days (p<0.05; RPa=1.09), appendiceal mass (p<0.05, RPa=1.18) and bandemia (p<0.05, RPa=1.12) were significantly associated with unsuccessful management results of the appendiceal plastron. Conclusion: There are epidemiological and clinical characteristics associated with the results of the management of the appendicular plastron.